PERADILAN SMALL CLAIM COURT (GUGATAN SEDERHANA) DALAM HUKUM ACARA PERDATA INDONESIA - PL Tobing (The Juris, 2021)
Small Claims Court is a mechanism for settling disputes quickly so examined in small claims court are certainly cases that simple. In Article 1 number 1 of the Supreme Court Regulation Number 2 of 2015 it is stated that the Settlement of Simple Lawsuits is defined as "the procedure for examining a civil lawsuit with a material claim value of a maximum of Rp. 200 million which is settled with simple procedures and proof". In addition to the provisions regarding the value of the lawsuit, of course there are other conditions for a case to be resolved through a small claim court. The research method uses normative juridical research, namely examining the application of the small claim court in civil procedural law in Indonesia. The type of research used in this research is descriptive analytical, namely legal research that observes the facts of a legal event in themechanism small claim court and then analyzes it. The results of the study show that the principles in civil procedural law in Indonesia are simple, fast and low cost. So far, this principle has not been implemented effectively because in practice the settlement of civil disputes always takes a long time and costs a lot of money. Meanwhile, in the settlement of a simple lawsuit, the maximum limit for the value of the material claim has been determined and the case submitted must be against the law or breach of contract, while in the settlement of cases through civil procedural law the material claim is not determined, and the case submitted does not have to be unlawful and tortuous.